Origin of the clock in Neurospora crassa - Al-Omari, Ahmad; Altimus, Cara; Arnold, Jonathan; Arsenault, Sam; Bhandarkar, Suchendra; Bhusal, Shishir; Caranica, Christian; Cheong, Jia Hwei; Deng, Zhaojie; Edison, Arthur S.; Floyd, Garrett; Griffith, James; et al. (Frontiers in Molecular Biosciences, 2026)
We examine the collective behavior of single cells in microbial systems to provide insights into the origin of the biological clock. Microfluidics has opened a window onto how single cells can synchronize their behavior. Four hypotheses are proposed to explain the origin of the clock from the synchronized behavior of single cells. These hypotheses depend on the presence or absence of a communication mechanism between the clocks in single cells and the presence or absence of a stochastic component in the clock mechanism. To test these models, we integrate physical models for the behavior of the clocks in single cells or filaments with new approaches to measuring clocks in single cells. As an example, we provide evidence for a quorum-sensing signal both with microfluidics experiments on single cells and with continuous in vivo metabolism NMR (CIVM-NMR). We also provide evidence for the stochastic component in clocks of single cells. Throughout this study, ensemble methods from statistical physics are used to characterize the clock at both the single-cell level and the macroscopic scale of 106 cells.